Film review Moromeții 3 [The Moromete Family 3], directed by Stere Gulea, 2024 - POP-CURȘEU, Ioan (Studia Universitatis Babeș-Bolyai Dramatica, 2024)
Stere Gulea’s latest film, Moromeții 3 [The Moromete Family 3], released on November 22 in Romanian cinemas after being screened for its premiere in the prestigious Romanian festival Tiff, concludes in a remarkable way a trilogy started in 1987 and proves the persistence of a dialogue between the art of film and one of the great novels of our literature, signed by Marin Preda. If the first movie of the trilogy was based on the first volume of the novel and if the second part, in 2018, focused on the second volume and on Viața ca o pradă [Life as a Prey], this third movie in the series does a pirouette and turns Niculae (played by Alex Călin) into the very author of Moromeții, trying to draw the precise context of the genesis of the novel. Moments from the process of collectivization of agriculture, from the life of writers subject to the Communist Party, or from Marin Preda’s love affairs, which become those of the fictional character he himself invented, are accurately re-created. The most significant affective inclination of Niculae/Preda is the relationship with his future wife, Aurora Cornu (played by Mara Bugarin), who plays a key role in the writer’s life, through her constant encouragement in the second part of the movie to print the manuscript of the novel.